DLT Compliance Reporting - Johannes Rude Jensen; Henrik Axelsen; Omri Ross (Complex Systems Informatics and Modeling Quarterly)
Today, local financial institutions are responsible for submitting compliance reporting data to the supervisory authorities. This is commonly referred to as the ‘push model’. The increasing complexity of reporting obligations often results in delayed reporting which delivers a fragmented and incomplete macroeconomic overview of the financial sector. Working with a group of nine representatives from industry and regulatory authorities, we employ the design science research methodology (DSR) in the design of an artefact, enabling the automated collection and enrichment of transactional data from DLT ledgers. Our findings demonstrate how the adoption of DLT in the financial sector will facilitate the automation of compliance reporting through a ‘pull-model’, in which regulators can access compliance data in near real-time and stage aggregate macroeconomic risk exposures for the eurozone. The findings contribute practical insights to the discourse on design-driven research on DLT and blockchain technology.